Antigen delivery by filamentous bacteriophage fd displaying an anti‐DEC‐205 single‐chain variable fragment confers adjuvanticity by triggering a TLR9‐mediated immune response. Issue 7 (17th April 2015) - Sartorius, Rossella; D'Apice, Luciana; Trovato, Maria; Cuccaro, Fausta; Costa, Valerio; De Leo, Maria Giovanna; Marzullo, Vincenzo Manuel; Biondo, Carmelo; D'Auria, Sabato; De Matteis, Maria Antonietta; Ciccodicola, Alfredo; De Berardinis, Piergiuseppe
Abstract Filamentous bacteriophage fd particles delivering antigenic determinants via DEC‐205 (fdsc‐αDEC) represent a powerful delivery system that induces CD8+ T‐cell responses even when administered in the absence of adjuvants or maturation stimuli for dendritic cells. In order to investigate the mechanisms of this activity, RNA‐Sequencing of fd‐pulsed dendritic cells was performed. A significant differential expression of genes involved in innate immunity, co‐stimulation and cytokine production was observed. In agreement with these findings, we demonstrate that induction of proinflammatory cytokines and type I interferon by fdsc‐αDEC was MYD88 mediated and TLR9 dependent. We also found that fdsc‐αDEC is delivered into LAMP‐1‐positive compartments and co‐localizes with TLR9. Thus, phage particles containing a single‐strand DNA genome rich in CpG motifs delivered via DEC‐205 are able to intercept and trigger the active TLR9 innate immune receptor into late endosome/lysosomes and to enhance the immunogenicity of the displayed antigenic determinants. These findings make fd bacteriophage a valuable tool for immunization without administering exogenous adjuvants.